EFFECT OF HYDROTHERAPY ON CHRONIC PAIN IN THE LUMBAR REGION - Mariya Gramatikova; Stamenka Mitova; Nasko Valchev (Peytchinski Publishing, 2020)
Purpose: To develop and study the effectiveness of methods and algorithms using a specialized magnetotherapy with underwater water-jet massage for chronic lumbar pain. Material/Methods: 30 subjects from two experimental groups (EG-1 from 15 athletes and EG-2 from 15 non-athletes) were examined, all with chronic lumbar pain. Testing is performed - before and after one month of physiotherapy. The test battery includes: anthropometry (height, body weight); visual-analogue pain scale; Laseg test - for the neurodynamics of n.ischiadicus. Physiotherapy includes hydrotherapy, with a water temperature of 360 - 370 and magnetotherapy with a duration of 30 - 35 min - treatment of the paravertebral muscle in the lumbar region, gluteus and lower limbs - dorsal and ventral. The procedures are applied 3 times a week for one month. Results: Methods and algorithms using a specialized magnetotherapy with underwater water-jet massage for patients with chronic lumbar pain have been developed. Pain on the Visual-Analog Scale of EG-1 athletes was studied - before physiotherapy (with hydrotherapy) X= 4.93±1.39mm, V% = 28.12%, which is an indicator of severe pain in the lumbar region. After 30 days, physiotherapy was reduced to X= 1.53±0.99mm, at V% = 64.59%. Its decrease is 31.03%, P<0.01. Pain beforehysiotherapy was found in EG-2 X= 6.87±1.64mm, at V% = 23.91%. After physiotherapy, it is reduced to X= 1.93±1.49mm, at V%=76.89%, P<0.01. A study of the neurodynamics of n.ischiadicus, through the Laseg test, found that passive flexion in the hip joint of the healthy leg - before physiotherapy with EG-1 hydrotherapy wasX=76.33±8.76o, at V% = 11.47%. After hydrotherapy increased to X= 86.33±5.51o, at V%=6.37%. Passive flexion in the hip joint of the injured leg before hydrotherapy was detected in EG-1. X= 69.67±10.43o, which indicates its strong limit. Post-hydrotherapy X= 80.33±10.08o, at V%=12.55%. P<0.0. In EG-2, the passive flexion in the hip joint - before hydrotherapy, the healthy leg was X= 71.67±14.1o, V% = 19.67%. After hydrotherapy increased to X= 81.53±8.37o. In V% = 10.26%. In the injured leg, passive flexion - before hydrotherapy wasv X= 71.00±11.37o, after it X= 82.07±7.70o, V% = 9.39%. P<0.01. Conclusion: The proven technique and algorithms of hydrotherapy, with a specialized with underwater water-jet massage, is effective for the recovery of persons with chronic lumbar pain. The technique reduces the neurological and pain symptoms and the restoration of n.ischiadicus.